Two new species of genus Mallomonas from swamp localities in Vietnam - Gusev, Evgeniy S.; Kulikovskiy, Maxim S. (Phytotaxa, 2020)
Two new species, Mallomonas punctostriata sp. nov. and Mallomonas collucata sp. nov., are described from Vietnam based on silica-scale morphology studied by means of transmission and scanning electron microscopy. Both species inhabits swamp areas. Mallomonas punctostriata belongs to section Striatae. Its scales have unique transverse rows, consisting of papillae, resembling transverse ribs of members of section Striatae. Mallomonas collucata belongs to section Annulatae. This species has small scales with hexagonal reticulation on the shield. Mallomonas punctostriata was found in Phu Quoc Island (Kien Giang Province) and Cam Ranh Peninsula (Khanh Hoa Province). Mallomonas collucata has been observed only in one site on Phu Quoc Island.